Architecture of the yeast origin recognition complex bound to origins of DNA replication. - Lee, D G (1997)
In many organisms, the replication of DNA requires the binding of a protein called the initiator to DNA sites referred to as origins of replication. Analyses of multiple initiator proteins bound to their cognate origins have provided important insights into the mechanism by which DNA replication is initiated. To extend this level of analysis to the study of eukaryotic chromosomal replication, we have investigated the architecture of the Saccharomyces cerevisiae origin recognition complex (ORC) bound to yeast origins of replication. Determination of DNA residues important for ORC-origin association indicated that ORC interacts preferentially with one strand of the ARS1 origin of replication. DNA binding assays using ORC complexes lacking one of the six subunits demonstrated that the DNA binding domain of ORC requires the coordinate action of five of the six ORC subunits. Protein-DNA cross-linking studies suggested that recognition of origin sequences is mediated primarily by two different groups of ORC subunits that make sequence-specific contacts with two distinct regions of the DNA. Implications of these findings for ORC function and the mechanism of initiation of eukaryotic DNA replication are discussed.